Officially supported export credits : developments and prospects - Dillon, K. Burke; Duran-Downing, Luis [Contributor]; Xafa, Miranda [Contributor]; International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
This book contains a study carried out by the International Monetary Fund with credit agencies and government authorities of the ten major industrial countries plus Spain during April and May 1987.
usc 18/4/2019
Loans
Keywords: Export credit; Economic forecasting